2016
DOI: 10.1021/acs.jpclett.6b00860
|View full text |Cite
|
Sign up to set email alerts
|

DNP-Enhanced Ultrawideline Solid-State NMR Spectroscopy: Studies of Platinum in Metal–Organic Frameworks

Abstract: Ultrawideline dynamic nuclear polarization (DNP)-enhanced (195)Pt solid-state NMR (SSNMR) spectroscopy and theoretical calculations are used to determine the coordination of atomic Pt species supported within the pores of metal-organic frameworks (MOFs). The (195)Pt SSNMR spectra, with breadths reaching 10 000 ppm, were obtained by combining DNP with broadbanded cross-polarization and CPMG acquisition. Although the DNP enhancements in static samples are lower than those typically observed under magic-angle spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 45 publications
1
79
1
Order By: Relevance
“…This induces a polarization transfer from the free electrons to the NMR nuclei, which significantly enhances the NMR sensitivity. This state‐of‐the‐art technique was shown to be an expedient tool to characterize solid materials, such as metal organic frameworks (MOFs),[33] periodic mesoporous silicates (PMOs), aluminosilicates,[35] and quantum dots . Here, all samples were prepared by incipient wetness impregnation of the zeolite with a 1,1,2,2‐tetrachloroethane (TCE) solution of a stable bulky 2,6‐spirocyclohexyl nitroxide derivative,[38] namely TEKPol .…”
Section: Resultsmentioning
confidence: 99%
“…This induces a polarization transfer from the free electrons to the NMR nuclei, which significantly enhances the NMR sensitivity. This state‐of‐the‐art technique was shown to be an expedient tool to characterize solid materials, such as metal organic frameworks (MOFs),[33] periodic mesoporous silicates (PMOs), aluminosilicates,[35] and quantum dots . Here, all samples were prepared by incipient wetness impregnation of the zeolite with a 1,1,2,2‐tetrachloroethane (TCE) solution of a stable bulky 2,6‐spirocyclohexyl nitroxide derivative,[38] namely TEKPol .…”
Section: Resultsmentioning
confidence: 99%
“…The recently developed WURST‐CPMG (wideband uniform rate smooth truncation with Carr–Purcell–Meiboom–Gill pulses) technique was also proven very useful for the study of ultra‐wideline patterns of metals. Huang and Pruski investigated the chemical bonding of platinum in MOFs by DNP‐enhanced WURST–CPMG . Combined with the theoretical calculations of the magnetic‐shielding tensors, they concluded that, in UIO‐66‐NH 2 , Pt 2+ ions, which are coordinated to the linkers in MOFs, are in both cis ‐ and trans ‐ conformations, whereas only the cis ‐ conformation was detected in the MOF‐253 ( Figure ).…”
Section: Interfaces In Nanocrystals and Quantum Dotsmentioning
confidence: 99%
“…b) Experimental (bottom) and simulated powder patterns for the cis (black) sites of Pt 2+ /MOF‐253. Reproduced with permission . Copyright 2016, American Chemical Society.…”
Section: Interfaces In Nanocrystals and Quantum Dotsmentioning
confidence: 99%
“…There have been many recent reports that include the use of metal SSNMR to characterize MOFs . Although metal centers are ubiquitous within MOFs and should serve as a convenient spectroscopic handle for SSNMR characterization, many MOFs feature multiple non‐equivalent metal sites that reside in similar chemical environments, which give rise to overlapping signals and pose a severe obstacle to metal SSNMR characterization.…”
Section: Resultsmentioning
confidence: 99%